PERSPEKTIF HUKUM TINDAK PIDANA HAK MERK INDUSTRI BATIK DI PEKALONGAN - Nuha, Ulin; Faozi, Safik (Universitas Stikubank, 2024)
Batik is a work of art that has unique cultural values. The existence of batik can be found at any time in all corners of the city of Pekalongan. Meanwhile, batik production and trading activities are active throughout the day, even late at night. The pulse of people's lives, which is never separated from batik, has given Pekalongan the image of a